Premature deaths attributable to blood pressure in China: a prospective cohort study - He, Jiang; Gu, Dongfeng; Chen, Jing; Wu, Xigui; Kelly, Tanika N; Huang, Jian-feng; Chen, Ji-chun; Chen, Chung-Shiuan; Bazzano, Lydia A; Reynolds, Kristi; Whelton, Paul K; Klag, Michael J (The Lancet (British edition), 2009)
Hypertension is a major global-health challenge because of its high prevalence and concomitant risks of cardiovascular disease. We estimated premature deaths attributable to increased blood pressure in China. We did a prospective cohort study in a nationally representative sample of 169 871 Chinese adults aged 40 years and older. Blood pressure and other risk factors were measured at a baseline examination in 1991 and follow-up assessment was done in 1999–2000. Premature death was defined as mortality before age 72 years in men and 75 years in women, which were the average life expectancies in China in 2005. We calculated the numbers of total and premature deaths attributable to blood pressure using population-attributable risk, mortality, and the population size of China in 2005. Hypertension and prehypertension were significantly associated with increased all-cause and cardiovascular mortality (p<0·0001). We estimated that in 2005, 2·33 million (95% CI 2·21–2·45) cardiovascular deaths were attributable to increased blood pressure in China: 2·11 million (2·03–2·20) in adults with hypertension and 0·22 million (0·19–0·25) in adults with prehypertension. Additionally, 1·27 million (1·18–1·36) premature cardiovascular deaths were attributable to raised blood pressure in China: 1·15 million (1·08–1·22) in adults with hypertension and 0·12 million (0·10–0·14) in adults with prehypertension. Most blood pressure-related deaths were caused by cerebrovascular diseases: 1·86 million (1·76–1·96) total deaths and 1·08 million (1·00–1·15) premature deaths. Increased blood pressure is the leading preventable risk factor for premature mortality in the Chinese general population. Prevention and control of this condition should receive top public-health priority in China. American Heart Association (USA); National Heart, Lung, and Blood Institute, National Institutes of Health (USA); Ministry of Health (China); and Ministry of Science and Technology (China).